Level set based method for design of compliant mechanisms - Jouve, François; Mechkour, Houari (European Journal of Computational Mechanics, 2008)
In the context of structural optimization, we propose two natural extensions of the level set method for the design of compliant mechanisms. Two new objective functions are introduced, well suited to the automatic design of compliant mechanisms, and a strategy for the design of mechanisms adapted to multiple loads is proposed. This work is illustrated with several numericals examples.